The Effect of Medicine Ball Throw Exercise on Volleyball Servicing Ability in Pusri Palembang Athletes - Anisa, Azola Dwi; Rahman, Andi; Junaidi, Ilham Arvan (Journal of Social Work and Science Education, 2023)
This experiment used a pretest-posttest control group design technique. The Quasi Experimental Design or Group Pretest Posttest Design was employed in this investigation. Athlete Pusri Palembang provided the sample for this study, which included 20 athletes. In the investigation, the retrieval procedure samples This approach employs random sampling. The findings of the study support the concept. Because the p0,000 value is less than 0.05, this indicates that medicine ball throw workouts have a substantial effect on Service Ability for Volleyball Games. Where posttest results have a higher average value than pretest scores. It is possible to infer that there is an affect technique Medicine Ball Throw exercise against Service Ability for Volleyball Games in Volleyball Club Athletes Pusri Palembang at the alpha level of 0.05 with a 95% confidence level.